Union Citizenship: A Furtive Spirit of Positive Peace Towards Industrial Peace - Santander, Noel Deseo; Prudente, Josephine (The Asian Journal of Technology Management (AJTM), 2020)
Abstract. Ascribing the attainment of positive peace to the voluntary active participation of the members in organized labor poses a great deal especially in attempting to attain an industrial peace. This research explores the problem of how union citizenship is considered as a furtive spirit of positive peace that can contribute to the development of industrial peace. It embraces a qualitative content analysis’ conventional methodology and process employed on the shared knowledge and experiences of the members of a trade or workers’ union, purposively chosen as respondents. The results presented the various duties and responsibilities of the respondents as union members. It conveyed the concrete expressions of union citizenship of the respondents, using the common behavioral determinants as categories, and the positive peace domains as major themes. It also provided the different possible contributions of union citizenship to the attainment of human development and industrial peace which was considered as an essential facet of nation-building. The results concluded with the call for promoting the union citizenship in any organized labor that will assist the workers and management to continuously work together and act as a catalyst of change to induce positive peace in the workplace and attain industrial peace.Keywords: Industrial Peace, Organizational Citizenship Behaviors, Positive Peace, Trade union, Union Citizenship.